2019
DOI: 10.1002/jcla.23000
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio and platelet‐to‐lymphocyte ratio are associated with disease activity in polymyalgia rheumatica

Abstract: Background The neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and monocyte‐to‐lymphocyte ratio (MLR) are indicators of systemic inflammation and are useful as markers in systemic rheumatic diseases. In this study, we compared the NLR, PLR, and MLR among patients with polymyalgia rheumatica (PMR) and rheumatoid arthritis (RA), and explored possible associations with clinical features, disease activity, and prognosis in patients with PMR. Methods The study enrolled 94 patients with PMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…Aside from that, NLR has been recognized as a marker of the systemic in ammatory response [8]. As such, NLR has been reported to re ect a heightened in ammatory reaction and has gained increasing attention as a prognostic marker in many conditions, such as solid tumors, in ammatory diseases, and postoperative infection [10,11,14]. A previous study reported that NLR was signi cantly higher in patients with polymyalgia rheumatica and was shown to be associated with disease activity and speci c clinical features [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from that, NLR has been recognized as a marker of the systemic in ammatory response [8]. As such, NLR has been reported to re ect a heightened in ammatory reaction and has gained increasing attention as a prognostic marker in many conditions, such as solid tumors, in ammatory diseases, and postoperative infection [10,11,14]. A previous study reported that NLR was signi cantly higher in patients with polymyalgia rheumatica and was shown to be associated with disease activity and speci c clinical features [10].…”
Section: Discussionmentioning
confidence: 99%
“…As such, NLR has been reported to re ect a heightened in ammatory reaction and has gained increasing attention as a prognostic marker in many conditions, such as solid tumors, in ammatory diseases, and postoperative infection [10,11,14]. A previous study reported that NLR was signi cantly higher in patients with polymyalgia rheumatica and was shown to be associated with disease activity and speci c clinical features [10]. Inose et al retrospectively investigated the association of NLR with the surgical site infection in 242 patients who underwent spinal instrumentation surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, NLR as an in ammation indicator has been well studied in various in ammation associated pathological conditions [10][11][12][13]. Higher NLR was correlated with more advanced disease stage in autoimmune disease [17,18] and it was proved to be an independent prognosis factor in infections disease [11,19], diffuse large B-cell lymphoma [20,21], and so on. Whilst, a higher NLR predicts increased 30-day mortality in critically ill patients [13,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In oncology, high NLR and PLR are associated with poor prognostic outcomes across a range of solid organ malignancies 3,4 . These indices have similarly been found to correlate with disease activity in several rheumatic diseases including most recently PMR, but their role in predicting treatment response in this condition is less well‐defined 5‐8 …”
Section: Introductionmentioning
confidence: 99%